ASPEK LINGKUNGAN SOSIAL DAN POTENSI MUNCULNYA PERILAKU PENAMBAHAN BORAKS DALAM PROSES PRODUKSI BAKSO DAGING SAPI DI KOTA PEKANBARU - Jully Handoko; Sofia Anita; Christine Jose (Jurnal Ilmu Lingkungan, 2010)
The study was aimed to identify and analyze social environmental aspects of beef meatballmerchants’s behaviour that is potencial to cause the case of borax content on meatball in Pekanbaru. Results of the study were expected to be a preliminary study about beef meatballmerchants’s profil in Pekanbaru that could be used as the guide of next studies in detail.The study was carried out during January 2010 in Pekanbaru. There were 128 beef meatballmerchants used as respondents taken by simple random and purposive throughout the city. Identification of social environmental aspects was done by using questionaire and researcher’sguidance to avoid mis-perception. It was a survey method to identify some aspects such as 1)age; 2) education; 3) selling experience; 4) duration of daily selling; 5) daily omset; 6)government; and 7) preference of beef meatball texture based on merchants. Data analysis wasdone by tabulation and descriptively showed by mean and percentage. Results of the study showed that most of beef meatball merchants in Pekanbaru Municipalitywere 34,8 years old on the average (productive age), have low formal education and 9 yearsselling experience on the average. They got Rp. 998.696,- daily omset on the average during 8hours of daily open. They also said that they didn’t get elucidation from the goverment and theirpreference of beef meatball texture were rubbery. The social environmental aspects werepotencial to emerge the behaviour of adding borax into beef meatball processing.